Functionality Evaluation and Testing of Web-Based Sparepart Sales System Using Black-Box Method - Syah, Rizky Firman; Utomo, Agus Prasetyo (Universitas Mohammad Husni Thamrin, 2025)
In recent decades, the rapid growth of information technology has encouraged various industries to adopt digital-based systems, including the automotive industry. Web-based information systems have become innovative tools for managing sales, inventory, and direct reports (H. Widiani, 2024). These systems enable fast and accurate data access and facilitate data-driven decision-making. Web-based systems enable more organized data management, which helps optimize business operations (Angelo & Ridho, 2022). In this digital era, customers today require fast and accurate service in the digital era. Web-based sales information systems play a crucial role in improving transaction efficiency and data management accuracy. This study evaluates the system's functionality at the Bagio Jaya Workshop using a black-box method with a quantitative descriptive approach through observation, interviews, and documentation. The evaluation focused on the system's feature completeness, functional effectiveness, and service quality. Test results showed that key features, such as Home, Customer Registration, Login, Spare Parts Search, Ordering, Payment, and Sales Reports, functioned according to specifications. The system can handle various input scenarios, both valid and invalid, thus improving the efficiency of sales data management. Furthermore, the intuitive interface facilitates ease of use for users with varying levels of technological literacy. In conclusion, the system functions optimally, improves operational efficiency, and provides user convenience. The results of this study are expected to contribute to the development of similar systems in various industrial sectors.